IMPLEMENTASI PROGRAM GEBYAR ANAK SHOLEH SEBAGAI UPAYA PENGUATAN KARAKTER RELIGIUS ANAK USIA DINI DAN SEKOLAH DASAR DI DESA TELUK MELINTANG - Maryam; Pahmi; Sofiatun Nisa; M. Kausar; Imroatul Pitri; Mayang Sari; Madani Futra; Eti Lastriani; Rita Yani; Solmah; Nur hapizin; Diki Nurdwiyanto (As-Sulthan Journal of Education, 2026)
The Community Service Program (KKN) is a form of student community service aimed at making a real contribution to social and educational development. One of the programs implemented was the